2017
DOI: 10.1002/adfm.201606821
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution and Magnetic Property of Rare‐Earth‐Doped Hematite Nanoparticles: Promising Contrast Agents for T1‐Weighted Magnetic Resonance Imaging

Abstract: A series of uniform rare‐earth‐doped hematite (α‐Fe2O3) nanoparticles are synthesized by a facile hydrothermal strategy. In a typical case of gadolinium (Gd)‐doped α‐Fe2O3, the morphology and chemical composition can be readily tailored by tuning the initial proportion of Gd3+/Fe3+ sources. As a result, the products are observed to be stretched into more elongated shapes with an increasing dopant ratio. As a benefit of such an elongated morphological feature and Gd3+ ions of larger effective magnetic moment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…It is believed that Gd ions have a high spin moment that can accelerate binding with water to shorten the longitudinal spin-lattice relaxation time of protons inside tissues. [35,57,92,206,207] This designed multifunctional RE doped nanoparticles as T 1 -T 2 dual-modal MRI contrast agents can change the signal intensity of the tumor site and improve the accuracy of MRI diagnosis at an early stage of all types of tumors. [208,209] In addition, these multifunctional nanoparticles can provide the difference in the signal intensity under different scanning sequences.…”
Section: Mri Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that Gd ions have a high spin moment that can accelerate binding with water to shorten the longitudinal spin-lattice relaxation time of protons inside tissues. [35,57,92,206,207] This designed multifunctional RE doped nanoparticles as T 1 -T 2 dual-modal MRI contrast agents can change the signal intensity of the tumor site and improve the accuracy of MRI diagnosis at an early stage of all types of tumors. [208,209] In addition, these multifunctional nanoparticles can provide the difference in the signal intensity under different scanning sequences.…”
Section: Mri Studiesmentioning
confidence: 99%
“…The white arrows refer to tumors injected with α-Fe 2 O 3 dispersions while the grey arrows stand for blank experiments. [206] Reproduced with permission. [57] Copyright 2016, Royal Society of Chemistry; Reproduced with permission.…”
Section: Mri Studiesmentioning
confidence: 99%
“…The bars representing the two magnetic phases, maghemite and hematite, are patterned. The saturation magnetization of bulk maghemite is 60 emu/g [35], whereas hematite is weakly ferromagnetic at room temperature [64]. Taking into account the lowering in magnetization that occurs due to the evolution of a dead magnetic layer on the surface of the particles at the nanoscale [65], it is observed that the magnetization is consistent with the crystal structure of the samples.…”
Section: Magnetic Measurementsmentioning
confidence: 80%
“…Mathevula et al [19] have shown the enhancement in optical properties with doping of Holmium (Ho). Wan et al [20] also reported the enhancement in magnetic properties with the incorporation of Gd +3 ions in -Fe2O3.Bhat et al [21] study the synthesis and optical studies of α-Fe2O3 and erbium (Er 3+ ) ion-doped α-Fe2O3 nanoparticles (NPs) and confirms the hexagonal (rhombohedral) crystal structure, with no additional phase formation.…”
Section: Introductionmentioning
confidence: 92%